Use Of Chiba Needle in Epidural Anesthesia: A Combined Spinal Epidural Anesthesia Technique - Dinesh Thakur; Chandralekha; Mihir Goswami (National Journal of Community Medicine, 2011)
Regional anesthesia offers safe, effective, and economical over general anaesthesia. Combined spinal epidural anesthesia (CSEA) has been used even for last two decades and involves the use of a minimal dose of spinal anesthetic for a shorter duration but allows flexibility of epidural reinforcement if necessary. CSEA technique has been used without any report of a unique or major complications attributed to the technique.1, 2 There are four main varieties of CSEA and a review of its history provides the opportunity to describe this sub – division.